PID Control: New Design Methods and Applications (IntechOpen, 2025)
The subjects in the book PID Control - New Design Methods and Applications chapters range from fundamental aspects of PID(Proportional–Integral–Derivative) controller design theory to industrial applications and complex process control systems. The book covers topics such as basic considerations for the digital implementation of PID Controllers, tuning methods of fuzzy PI controllers, analytical design of a closed control loop controller, identification and control of unstable systems using PITOPS(Process Identification and Controller Tuning Optimizer Simulator), and the design and development of servo drive control system based on DSP(Digital Signal Processor) The book highlights several advantages, including the efficiency of PID (Proportional–Integral–Derivative) controllers, which is demonstrated both theoretically and practically, showcasing their fast and stable response. It also emphasizes their ability to reduce errors and improve the performance of control systems, as well as their simplicity, ease of tuning, and the practical methods presented to enhance PID controllers. The book is intended for a broad audience, including academics and industrial specialists such as professors, researchers, designers, and students.